Perancangan Job Seeker - Aplikasi Pencari Kerja Menggunakan PHP dan MYSQL - Kurnia, Rahmi Putri; Sy, Yulia Jihan; Zalmi, Wahyuni Fithratul (UIN Imam Bonjol Padang, 2024)
Job vacancies are information that is really needed by many people with a very fast update rate, because it is related to the acceptance deadline. Speed of information and suitability of abilities are basic criteria in the job search process when applying for jobs. However, the distribution of this information is quite difficult to obtain when you have to look for the source of the information in certain places first. For this reason, a solution is needed to simplify these difficulties. The software development methodology used in the system development process is the waterfall methodology. In this methodology, several steps are taken to build software, namely software engineering, system analysis, system design, system implementation, system testing. By carrying out stages based on the methodology, it is hoped that the application will be built according to needs and can be used by consumers. The Job Seeker Application is an application that can help disseminate job vacancy information for job seekers and employers to assist the job application process directly for job seekers.